Meeting place, meeting people - Clayton, Iris.; Jewell, Bronwyn (Canberra, A.C.T. : PhotoAccess, 1997)
"A collection of stories and photographs of Aboriginal people in the ACT" -- t.p. verso.
"A collection of stories and photographs of Aboriginal people in the ACT" -- T.p. verso.
Keywords: Aboriginal Australians -- Interviews; Aboriginal Australians -- Biography; History - Biographies; Canberra (ACT SI55-16)